The nexus between Indonesia’s exchange rate and the world crude palm oil price - Cheng-Wen Lee; Andrian Dolfriandra Huruta (International Entrepreneurship Review, 2019)
Objective: International trade plays a major role in increasing the output of each country. Crude Palm Oil (CPO) is one of Indonesia’s major export commodities. Facts show over the past two decades, CPO has become a fast-growing product. However, there are obstacles from one of Indonesia’s CPO importers, namely the European Union. The aim of this study is to explore the nexus between the exchange rate and the world price of CPOs.